Women's decision-making power in a context of free reproductive healthcare and family planning in rural Burkina Faso - Camille Beaujoin; Alice Bila; Frank Bicaba; Véronique Plouffe; Abel Bicaba; Thomas Druetz (BMC, 2021)
Abstract Background In 2016, the national user fee exemption policy for women and children under five was introduced in Burkina Faso. It covers most reproductive healthcare services for women including prenatal care, delivery, and postnatal care. In subsequent years, the policy was gradually extended to include family planning. While studies have shown that user fee abolition policies increase visits to health centers and improve access to reproductive healthcare and family planning, there are also indications that other barriers remain, notably women's lack of decision-making power. The objective of the study is to investigate women's decision-making power regarding access to reproductive health and family planning in a context of free healthcare in rural Burkina Faso. Methods A descriptive qualitative study was carried out in rural areas of the Cascades and Center-West regions. Qualitative data were collected using individual semi-structured interviews (n = 20 participants) and focus groups (n = 15 participants) with Burkinabe women of childbearing age, their husbands, and key informants in the community. Data was analyzed using thematic analysis. Results A conceptual framework describing women's participation in the decision-making process was built from the analysis. Results show that the user fee exemption policy contributes to improving access to reproductive care and family planning by facilitating the negotiation processes between women and their families within households. However, social norms and gender inequalities still limit women's decision-making power. Conclusion In light of these results, courses of action that go beyond the user fee exemption policy should be considered to improve women's decision-making power in matters of health, particularly with regard to family planning. Interventions that involve men and community members may be necessary to challenge the social norms, which act as determinants of women's health and empowerment.